The relationship of Taro (Colocasia esculenta (L.) Schott) in Kubu Raya Regency, West Kalimantan based on morphological characters - Sari, Lestari Indah; Wardoyo, Elvi Rusmiyanto Pancaning; Ifadatin, Siti (Buletin Kebun Raya, 2023)
Taro (Colocasia esculenta (L.) Schott) belongs to the Araceae family and has long been cultivated in Indonesia. Taro was widespread and easy to grow anywhere in West Kalimantan. This research aimed to observe the variability and the relationship of taro in Kubu Raya Regency, West Kalimantan Province, based on morphological characters. The research was carried out from September to November 2020. The sampling of 48 samples in 9 subdistricts used a purposive sampling method. Relationship analysis of 44 morphological characters, including 33 qualitative characters and 11 quantitative characters, used the UPGMA method. The results showed that the 48 taro accessions had a similarity coefficient value of 0.49 or 49%, which were divided into 4 clusters. The morphological characterization showed that taro accessions had high phenotypic diversity. The leaves and tubers showed the most varied character.